Examining the effect of phonological awareness instruction on EFL learners’ pronunciation and motivation - I Ketut Wardana; Putu Tri Astuti; Ni Luh Sukanadi (Erudita: Journal of English Language Teaching, 2022)
ELT teachers in Indonesia mostly apply an integrative language teaching approach to cover the linguistic elements of language skills. However, the pronunciation in speaking exposure is required to be accurate through the intervention of phonological awareness. Thus, this study examines the effect of phonological awareness on students’ English pronunciation and how it provokes students’ motivation in speaking English. This study used a pretest-posttest control group design. The experimental group which consisted of 36 participants was given a phonological awareness intervention and the control group which consisted of 36 participants was given without any intervention. The instruments of the study were a text reading-aloud task and a questionnaire. Data were then analyzed using Pearson correlation and independent sample t-test. The findings revealed that phonological awareness instruction positively impacted participants’ pronunciation performance with better phonemes articulation, more appropriate stress determination, and more adequate intonation that directly provoked their speaking motivation. Therefore, EFL teachers should determine the phonological awareness approach for the potential English competence and performance integrated into the learning syllabus more intensively.